Lock-in inductive thermography for surface crack detection in different metals. Issue 3 (2nd October 2019) - Oswald-Tranta, B.
ABSTRACT: Inductive thermography is a non-destructive technique for detecting surface cracks in electrically conductive materials. The induced eddy currents and the heat diffusion are disturbed by surface cracks, which makes the defects visible in infrared images. In non-magnetic materials, with high electrical and thermal conductivity, a short heating pulse is necessary, otherwise the thermal signal diminishes too quickly. However, with a short heating pulse only a little amount of heat is induced into the material, so the noise may be too high compared to the signal, causing a too low signal-to-noise (SNR) ratio for reliable defect detection. Applying a sequence of short pulses offers a solution. The evaluation of this multi-pulse excitation is in principle identical to the well-known lock-in technique, which is usually applied for sinusoid modulated heating. The main goal of the paper is to investigate how the temperature and phase noise can be reduced by several factors. The influence of the number of pulses, the heating power, the pulse duration, and the crack depth on the SNR is investigated. Theoretical considerations and experimental results are presented and compared to the derived equations. Aluminum and non-magnetic steel samples with artificial cracks were inspected and compared to the theoretical results.